Development and validation of an In Vitro Release Test (IVRT) to investigate the release of miconazole nitrate from topical cream formulations - Purazi, Potiwa (Rhodes University, Faculty of Pharmacy, Pharmacy, 2017)
Expected release date-May 2019
Keywords: Uncatalogued